Black Zion: African American religious encounters with Judaism - Chireau, Yvonne Patricia; Deutsch, Nathaniel (Religion in America series, 2000)
Black culture and black Zion : African American religious encounters with Judaism, 1790-1930, an overview /Yvonne Chireau --African American Jews : dispelling myths, bridging the divide /Bernard J. Wolfson --Symbolic identity formation in an African American religious sect : the Black Hebrew Israelites /Merrill Singer --Another exodus : the Hebrew Israelites from Chicago to Dimona /Ethan Michaeli --Proximate other : the Nation of Islam and Judaism /Nathaniel Deutsch --Nubian Islaamic Hebrews, Ansaaru Allah Community : Jewish teachings of an African American Muslim community /Kathleen Malone O'Connor --Remembering Nehemiah : a note on Biblical theology /Allen Dwight Callahan --Theological affinities in the writings of Abraham Joshua Heschel and Martin Luther King, Jr. /Susannah Heschel --This is the gateway to the Lord : the legacy of synagogue buildings for African American churches on Cincinnati's Reading Road /Karla Goldman --"Jew" in the Haitian imagination : pre-modern anti-Judaism in the postmodern Caribbean /Elizabeth A. McAlister.